Production and characterization of chitosan-polyanion nanoparticles by polyelectrolyte complexation assisted by high-intensity sonication for the modified release of methotrexate (2020)
ABSTRACT: A promising strategy to improve the effectivity of anticancer treatment and decrease its side effects is to modulate drug release by using nanoparticulates (NPs) as carriers. In this study, methotrexate-loaded chitosan–polyanion nanoparticles were produced by polyelectrolyte complexation assisted by high-intensity sonication, using several anionic polymers, such as the sodium and potassium salts of poly(maleic acid-alt-ethylene) and poly (maleic acid-alt-octadecene), here named PAM-2 and PAM-18, respectively. Such NPs were analyzed and characterized according to particle size, polydispersity index, zeta potential and encapsulation efficiency. Likewise, their physical stability was tested at 4 ◦C and 40 ◦C in order to evaluate any change in the previously mentioned particle parameters. The in vitro methotrexate release was assessed at a pH of 7.4, which simulated physiological conditions, and the data were fitted to the heuristic models of order one, Higuchi, Peppas–Sahlin and Korsmeyer–Peppas. The results revealed that most of the MTX-chitosan–polyanion NPs have positive zeta potential values, sizes <280 nm and monodisperse populations, except for the NPs formed with PAM-18 polyanions. Further, the NPs showed adequate physical stability, preventing NP–NP aggregation. Likewise, these carriers modified the MTX release by an anomalous mechanism, where the NPs formed with PAM-2 polymer led to a release mechanism controlled by diffusion and relaxation, whereas the NPs formed with PAM-18 led to a mainly diffusion-controlled release mechanism.